Enraizamento de miniestacas e seleção de Cordia trichotoma (Vellozo) Arrabida ex Steudel para a propagação por miniestaquia - Somavilla, Tamires Manfio (2018)
The aim of this work was to study the mini-cutting rooting and to develop selection strategies of cordia (Cordia trichotoma) for asexual propagation by mini-cuttings. The effects of substrate, IBA concentration, mini-cutting size and time of year were evaluated in the capability of mini-cuttings adventitious rooting. Two experiments were carried out to evaluate the effect of four substrate compositions (commercial substrate, coarse sand and vermiculite, pure commercial substrate, commercial substrate, charcoal rice husk and sand, commercial substrate and vermiculite) and five concentrations (0; 1,500; 3,000; 4,500 or 6,000 mg L-1) of AIB in the rooting of single-bud mini-cuttings. Two experiments were carried out to evaluate the effect of size (smaller than 5 cm, between 5.1 and 10.0 cm, between 10.1 and 15.0 cm and bigger than 15.1 cm) and the same concentrations of IBA in the apical mini-cuttings rooting. Another experiment was carried out to evaluate the effect of the time of the year in the apical mini-cuttings rooting. In order to define an early selection strategies and to identify cordia clones with adventitious rooting capability, apical mini-cuttings were collected in one mini-stump of 30 clones and four mini-stumps of 19 clones. The number of mini-cuttings per mini-stump, the rooting percentage and the number of rooted mini-cutings per mini-stump were recorded. The substrate composition did not affect mini-cuttings rooting. Apical mini-cuttings up to 10 cm in length treated with 3,000 mg L-1 of AIB presented the greatest rooting capability, especially when collected during the summer season. Mini-cuttings size affects rooting potential and apical mini-cuttings are more responsive to adventitious rooting than single-bud ones. Cordia clones were identified based upon two strategies, being selected four and nine from 30 evaluated in one mini-stump, and three and seven from 19 clones evaluated in four mini-stumps. The selection gains were high (between 67.2 and 142.3%), both for rooting percentage and number of rooted mini-cuttings. Early selection is an efficient breeding strategy for adventitious rooting capability, and can be applied in one evaluated mini-stump per clone.